The contribution of maternal psychological functioning to infant length of stay in the Neonatal Intensive Care Unit - Cherry AS; Mignogna MR; Roddenberry Vaz A; Hetherington C; McCaffree MA; Anderson MP; Gillaspy SR (Dove Medical Press, 2016)
Amanda S Cherry,1 Melissa R Mignogna,1 Angela Roddenberry Vaz,1 Carla Hetherington,2 Mary Anne McCaffree,2 Michael P Anderson,3 Stephen R Gillaspy1 1Section of General and Community Pediatrics, Department of Pediatrics, University of Oklahoma Health Sciences Center, Oklahoma City, OK, 2Neonatal Perinatal Medicine, Department of Pediatrics, University of Oklahoma, College of Medicine, Oklahoma City, OK, 3Department of Biostatistics and Epidemiology, University of Oklahoma Health Sciences Center, College of Public Health, Oklahoma City, OK, USA Objective: Assess maternal psychological functioning within the Neonatal Intensive Care Unit (NICU) and its contribution to neonate length of stay (LOS) in the NICU.Study design: Mothers of infants admitted to the NICU (n=111) were assessed regarding postpartum depression, postpartum social support, postpartum NICU stress, and maternal anxiety at 2 weeks postpartum. Illness severity was assessed with the Clinical Risk Index for Babies (CRIB).Results: Postpartum depression was not significantly correlated with LOS, but was significantly correlated with trait anxiety (r=0.620), which was significantly correlated with LOS (r=0.227). Among mothers with previous mental health history, substance abuse history and CRIB score were the best predictors of LOS. For mothers without a prior mental health issues, delivery type, stress associated with infant appearance, and CRIB scores were the best predictors of LOS. In this group, LOS was found to increase on average by 7.06 days per one unit increase in stress associated with infant appearance among mothers with the same delivery type and CRIB score.Conclusion: Significant correlations of trait anxiety, stress associated with infant appearance, and parental role with LOS support the tenet that postpartum psychological functioning can be associated with NICU LOS. Keywords: NICU, postpartum depression, postpartum anxiety, parental stress, CRIB